Risk factors and abnormal cerebrospinal fluid associate with cognitive symptoms after mild COVID‐19. Issue 2 (19th January 2022) - Apple, Alexandra C.; Oddi, Alexis; Peluso, Michael J.; Asken, Breton M.; Henrich, Timothy J.; Kelly, J. Daniel; Pleasure, Samuel J.; Deeks, Steven G.; Allen, Isabel Elaine; Martin, Jeffrey N.; Ndhlovu, Lishomwa C.; Miller, Bruce L.; et al.
Abstract: Cognitive post‐acute sequelae of SARS‐CoV‐2 (PASC) can occur after mild COVID‐19. Detailed clinical characterizations may inform pathogenesis. We evaluated 22 adults reporting cognitive PASC and 10 not reporting cognitive symptoms after mild SARS‐CoV‐2 infection through structured interviews, neuropsychological testing, and optional cerebrospinal fluid (CSF) evaluations (53%). Delayed onset of cognitive PASC occurred in 43% and associated with younger age. Cognitive PASC participants had a higher number of pre‐existing cognitive risk factors (2.5 vs. 0; p = 0.03) and higher proportion with abnormal CSF findings (77% vs. 0%; p = 0.01) versus controls. Cognitive risk factors and immunologic mechanisms may contribute to cognitive PASC pathogenesis.